The public health consequences of mandatory return migration: a call for action - Izquierdo-Condoy, Juan S.; Salazar-Aguilar, José Pablo; Vasconez-Gonzalez, Jorge; Ortiz-Prado, Esteban (Frontiers in Public Health, 2025)
Migration has long shaped human societies, often generating complex social and political dynamics. In the United States, migration from Latin America represents a significant proportion of inflows, but increasingly restrictive policies have intensified hardships for migrants. Returning migrants frequently encounter systemic barriers such as limited healthcare access, economic instability, and social exclusion, all of which contribute to widening health disparities. The “healthy migrant effect” often declines as migrants face limited medical resources, reintegration difficulties, and weakened social support networks, which heighten the risk of mental health issues such as depression and PTSD. Moreover, food insecurity, poor living conditions, and exposure to violence further exacerbate physical and mental health vulnerabilities. Forced return migration magnifies these risks, leading to the marginalization of returnees both socially and economically. Addressing these challenges requires coordinated, equity-focused migration policies that integrate public health, legal, and social support systems. Sustainable, rights-based approaches are essential to promoting the long-term wellbeing of migrants and achieving broader public health goals.